IMPROVING STUDENTS’ SPEAKING SKILL BY USING DAILY VLOG AT SMAN 1 ENREKANG - Fitra P, Helsa; Rampeng, Rampeng; Syam, Ulfa (Publikasi dan UKI Press UKI Toraja., 2023)
This research aimed to know there in any significant improving using Daily Vlog on students’ speaking skill in class XI SMAN 1 Enrekang. This study focused on pre-experimental research one group pre-test and post-test. The population in this research were students of class XI SMAN 1 Enrekang. The researcher took 334 students as the population. The sampling is students of second-grade IPA 1 with totaling 23 students. Data obtained from speaking test. The result of this study used inferential analysis of the t-test by SPSS v.21, which showed a significant improving on the students’ mean score speaking skill between pre-test and post-test. The mean score of the students’ speaking enhanced from 44,26 in pre-test to 78,26 in the post-test. Thus, it can be concluded that there is significant improving Using Daily Vlog on students’ speaking skill in class XI at SMAN 1 Enrekang